2016
DOI: 10.1111/gcb.13565
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐induced glacier and snow loss imperils alpine stream insects

Abstract: Climate warming is causing rapid loss of glaciers and snowpack in mountainous regions worldwide. These changes are predicted to negatively impact the habitats of many range-restricted species, particularly endemic, mountaintop species dependent on the unique thermal and hydrologic conditions found only in glacier-fed and snow melt-driven alpine streams. Although progress has been made, existing understanding of the status, distribution, and ecology of alpine aquatic species, particularly in North America, is l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(103 citation statements)
references
References 59 publications
3
100
0
Order By: Relevance
“…yond those previously described(Baumann & Call, 2012;Baumann & Kondratieff, 2010;Giersch et al, 2016;Jordan et al, 2016;Muhlfeld et al, 2011). Phylogenetic analyses strongly supported the existing, morphology-based Lednia taxonomy with PPs of 1.0 for all nodes and described species resolved as monophyletic (Figure 3b).…”
supporting
confidence: 75%
See 1 more Smart Citation
“…yond those previously described(Baumann & Call, 2012;Baumann & Kondratieff, 2010;Giersch et al, 2016;Jordan et al, 2016;Muhlfeld et al, 2011). Phylogenetic analyses strongly supported the existing, morphology-based Lednia taxonomy with PPs of 1.0 for all nodes and described species resolved as monophyletic (Figure 3b).…”
supporting
confidence: 75%
“…In contrast, very few Lednia adults have been collected earlier than mid-August (Baumann & Call, 2012;Baumann & Kondratieff, 2010;Giersch et al, 2015Giersch et al, , 2016, and L. tumana adults have been collected into October (Baumann & Kondratieff, 2010 Beerli and Palczewski (2010). In contrast, very few Lednia adults have been collected earlier than mid-August (Baumann & Call, 2012;Baumann & Kondratieff, 2010;Giersch et al, 2015Giersch et al, , 2016, and L. tumana adults have been collected into October (Baumann & Kondratieff, 2010 Beerli and Palczewski (2010).…”
Section: Discussionmentioning
confidence: 99%
“…Groundwater microorganism metabarcoding studies have shown high fungal (Sohlberg et al, 2015) and bacterial (Kao et al, 2016) (Valiere & Taberlet, 2000). Environmental DNA metabarcoding of water from glacial run-off will also likely be a valuable tool to survey animal and plant richness living in glacial and subglacial habitats, which are undergoing dramatic change because of climate warming (Giersch, Hotaling, Kovach, Jones, & Muhlfeld, 2017).…”
Section: Species Relative Abundance: Edna Metabarcoding Compared Wimentioning
confidence: 99%
“…Lednia tumana inhabits short sections (~500 m) of cold, meltwater streams directly below glaciers, permanent snowfields and groundwater‐fed springs (Giersch et al., ; Muhlfeld et al., ). As glaciers and permanent snowpack decline, L. tumana 's range is expected to contract by more than 80% (Giersch et al., ; Muhlfeld et al., ). Historical and contemporary patterns of genetic diversity and demographic history for L. tumana however, remain explored.…”
Section: Introductionmentioning
confidence: 99%